2019
DOI: 10.1080/14786419.2019.1614576
|View full text |Cite
|
Sign up to set email alerts
|

A new pyrrole alkaloid from the roots of Cissampelos pareira

Abstract: Phytochemical investigation of the roots of Cissampelos pareira Linn. led to the isolation of one new pyrrole alkaloid, cissampeline (1), together with ten known alkaloids, (-)-curine (2), (-)-cyclanoline (3), (+)-tetrandrine (4), (+)-obaberine ( 5), (+)-obamegine ( 6), (-)-oblongine ( 7), (+)-homoaromoline ( 8), (-)-nor-N ‫׳‬ -chondrocurine (9), trans-N-feruloyltyramine (10) and (+)-coclaurine (11). Their structures were elucidated by extensive NMR and MS spectroscopic analyses. Interestingly, compound 1 repr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 16 publications
0
18
0
Order By: Relevance
“…Among them, hayatinine ( 20 ), isochondrondendrine ( 25 ), pelosine ( 28 ) and warifteine exhibited affinities to the inhibiting enzymes MAPK p38 alpha, PKC beta, PKC theta and PKC zeta. In contrast, the cissampeloflavone ( 81 ) had no potential inhibitory activity against PKC zeta or had no affinity for the PKC alpha [20] . In a paw edema model, milonine ( 60 ) extracted from C. sympodialis inhibited histamine release of activated mast cells [71] .…”
Section: Pharmacological Activitiesmentioning
confidence: 99%
See 3 more Smart Citations
“…Among them, hayatinine ( 20 ), isochondrondendrine ( 25 ), pelosine ( 28 ) and warifteine exhibited affinities to the inhibiting enzymes MAPK p38 alpha, PKC beta, PKC theta and PKC zeta. In contrast, the cissampeloflavone ( 81 ) had no potential inhibitory activity against PKC zeta or had no affinity for the PKC alpha [20] . In a paw edema model, milonine ( 60 ) extracted from C. sympodialis inhibited histamine release of activated mast cells [71] .…”
Section: Pharmacological Activitiesmentioning
confidence: 99%
“…Previous chemical investigations have showed that alkaloids were the major secondary metabolites of the genus Cissampelos. Up to now, a total number of80 alkaloids have been isolated and identified from C. pareira [20] toberberinic alkaloids (62-65), five tropoloisoquinolinic alkaloids (66)(67)(68)(69)(70), two azafluorantene alkaloids (71 -72), two stephaoxocane alkaloids (73)(74), three pro-aporphic alkaloids (75 -77) one monoterpenoid indole alkaloid (78), one phenylethylamine alkaloid (79) and one pyrrolidine alkaloid (80).…”
Section: Alkaloidsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this respect, the more deadly poisons were, the better they would be for the weapons to kill or Preserved-lingering issues of facts. EduLite: Journal of English Education,Literature,and Culture,6 (2), 397-410. http://dx.doi.org/10.30659/e.6.2.397-410 injure hunts or enemies (Rukachaisirikul et al, 2021;van Huis, 2021;Zvejniece et al, 2021). Therefore, in fighting between tribes for example each of them was extremely careful not to be scratched by even the slightest injury as it might lead to the death due to the danger of the poison.…”
Section: Introductionmentioning
confidence: 99%